Prevalence of Anemia among Patients with Diabetes Mellitus Attending a Tertiary care Center in Nepal: A Descriptive Cross-sectional Study - Adhikari, P; Acharya, A; Bhattarai, K Kritika; Gaire, S (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Anemia is a common yet often underdiagnosed complication in individuals with diabetes mellitus (DM), associated with increased risk of microvascular and macrovascular complications. Despite the growing burden of diabetes in Nepal, limited data exist on the prevalence of anemia in this population. This study aimed to determine the prevalence of anemia among patients with DM and explore its association with glycemic control and other clinical parameters. Methods: A descriptive cross-sectional study was conducted from April to October 2024 at Nepal Medical College Teaching Hospital. A total of 373 diabetic patients were enrolled using convenient sampling. Hemoglobin levels were assessed to diagnose anemia based on WHO criteria (<13 g/dL in males, <12 g/dL in females). Data on glycemic control (HbA1c), duration of diabetes, BMI, comorbidities, and treatment regimens were collected. Statistical analyses included chi-square tests, Mann-Whitney U tests, Kruskal-Wallis tests, and Spearman correlation. Results: Anemia was present in 123 (33%) of the 373 patients. Among anemic individuals, 67% had uncontrolled DM (HbA1c >7%). No significant association was found between anemia severity and glycemic control (p = 0.22). Anemia was significantly associated with gender (p = 0.001), BMI (p = 0.001), hypertension (p < 0.001), and thyroid dysfunction (p = 0.006), but not with dyslipidemia (p = 0.062). Duration of diabetes showed a significant association with glycemic control (p = 0.009) but not with anemia severity. Patients receiving oral hypoglycemic agents had significantly higher anemia severity compared to those on insulin therapy (p < 0.05). Conclusion: Anemia is a common comorbidity in diabetic patients in Nepal, especially among females and those with hypertension or thyroid dysfunction. Routine screening for anemia in diabetic patients is recommended to enable timely management.